Adropin and circadian variation of blood pressure - Bolayir, Hasan Ata; Kivrak, Tarik; Gunes, Hakan; Bolayir, Asli; Karaca, Ilgin (Via Medica, 2018)
Background: Nocturnal hypertension and non-dipping pattern are often associated with endothelial dysfunction. Previous studies suggested that adropin, a novel secreted energy homeostasis protein, has the unique ability to regulate endothelial cell function. Aim: This study aims to investigate the association between absolute night-time blood pressure (BP) and circadian BP pattern with serum adropin and high-sensitivity C-reactive protein (hsCRP) levels in patients with newly diagnosed untreated arterial hypertension. Methods: Twenty-four-hour ambulatory BP monitoring was recorded in 100 hypertensives (50 dippers, 50 non-dippers) and 50 healthy controls. Serum levels of adropin and hsCRP were measured and recorded. Results: A strong correlation was found between night-time BP levels with adropin and hsCRP levels (p < 0.001). On the other hand, the non-dipper group demonstrated lower adropin levels compared to the dipper and normotensive groups: non dipper group, 2580 +/- 457 pg/mL; dipper group, 3298 +/- 530 pg/mL; normotensive group, 3681 +/- 411 pg/mL; p < 0.001). HsCRP levels were significantly higher in the non-dipper group than in the two other groups (p = 0.017). In a multivariate logistic regression analysis, adropin (p = 0.012) and hsCRP (p = 0.039) were independently associated with a non-dipping pattern. Conclusions: Decreased adropin levels were found in the nocturnal hypertensive and non-dipper groups. Adropin and hsCRP were found to be independently associated with a non-dipping pattern. We suggest that decreased levels of adropin in non-dipper hypertensive patients might be associated with a longer duration of exposure to high BP. These results point to a possible future role of adropin in identifying hypertensive patients at higher risk of target organ damage.
Keywords: adropin; high-sensitivity C-reactive protein; dipper; non-dipper hypertension